Peran Niat Pembelian Online Pada Media Sosial Instagram: Mediasi Advertising Attitude dan Advertising Clicks - Wijaya, Siswoyo Ari; Heruwasto, Ignatius (Research Center and Case Clearing House PPM School of Management, 2024)
The rapid growth of social media users in Indonesia has prompted researchers to identify factors that impact consumer purchase intentions through advertising click activities, such as informativeness, entertainment, irritation, emotional appeal, credibility, and privacy concerns mediated by advertising attitude. This research examines how informativeness, entertainment, emotional appeal, and privacy concerns simultaneously influence attitudes toward advertising and purchase intentions. This study employed a quantitative approach through an online survey with a sample of 321 respondents residing in major cities in Indonesia. This study applied purposive sampling with individual criteria as Instagram users were exposed to ads within the last month, and the data were analyzed through structural equation modeling. The results of this study show that advertising attitude fully mediates informativeness, entertainment, emotional appeal, and credibility toward advertising clicks, which drive purchase intentions. Meanwhile, irritation and privacy concerns have a negative impact on advertising attitudes. This research proved that Incentives have a direct influence on purchase intention. Suggestions for future researchers need to consider the classification of ad product or service categories so that advertisers can better understand consumer behavior and provide ad impression effectiveness according to the target audience